Do physicians discuss end-of-life decisions with family members? A mortality follow-back study. Issue 8 (August 2018) - Vermorgen, Maarten; De Vleminck, Aline; Deliens, Luc; Houttekier, Dirk; Spruytte, Nele; Van Audenhove, Chantal; Cohen, Joachim; Chambaere, Kenneth
Highlights: In more than a quarter of ELD discussions preceding death, family is not involved. Family involvement in such discussions is context-dependent in current practice. Palliative care including focus on family is not yet omnipresent in healthcare. Abstract: Objective: Deaths from chronic illness are often preceded by a potentially life-shortening end-of-life decision (ELD). Involving family in these ELDs may have psychosocial benefits for them and the dying person. This study aims to examine how often ELDs are discussed with relatives of the dying person and which characteristics determine their involvement in those ELDs. Methods: A questionnaire survey was conducted in 2013 among physicians attending a large, stratified and representative sample of deaths (n = 6188) in Flanders. Results: In 72.3% of ELDs preceding death, family of the dying person were involved. Discussion of an ELD with family members was more likely when the decision was also discussed with the dying person, the ELD was made with the explicit intention to shorten life, specialized palliative care was provided or death occurred in an ICU. Conclusions: Involving family in end-of-life decision making appears to be related to the type of formal care services involved, communication with the dying person and the motives behind the decision. Practice implications: Our findings suggest a need to further expand a palliative care approach with a focus on both the dying person and their family within and across a variety of health care services.